Serbia through the Lens of Small States’ Foreign Policy. Balancing between the European Union and the Russian Federation - Jan Graf; Martin Solik (Romanian Journal of European Affairs)
The small states’ foreign policy has long been a neglected topic in academic circles because the very definition of “small state” was discussed only after World War II. However, in the accelerated dynamics of global security, foreign policy of small states is gradually gaining importance. This study aims to clarify Serbia’s foreign policy orientation in the context of the security developments related to the Russian aggression in Ukraine, which has forced many states to reassess their security policy. Using a case study approach, the authors seek to highlight if Serbia’s foreign policy is built on the general premises of the small states’ foreign policy, and how its specific features enable Serbia’s balancing act. For this purpose, three characteristics of the small states’ foreign policy have been selected: military neutrality, efforts to join international organisations, and the commitment to fully respect international law. Based on expert interviews and the analysis carried out, the authors conclude that Serbia contradicts two theoretical assumptions about the foreign policy of these states, a fact that paradoxically helps Belgrade maintain close relations with both Brussels and Moscow. However, due to the Russian-Ukrainian conflict, an easier path to the EU opens for Belgrade, and this type of foreign policy could therefore come to an end.